2006
DOI: 10.1002/kpm.260
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ambiguity on project task structure in new product development

Abstract: New product development (NPD) projects are characterised by task ambiguity, whereby the set of tasks necessary for project completion and the relationships between tasks are initially unknown and only emerge as the development process unfolds. This paper uses interview data from NPD project managers in a large telecom firm to examine the influence of product requirements ambiguity on NPD task structures. The findings are used to propose a taxonomy outlining four generic patterns by which NPD task structures ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This section reports on the most salient empirical studies in the literature. Duimering et al (2006) found that project task structure changes as a function of ambiguity. Carbonell and Rodriguez (2006) found a moderating influence of technical complexity on staffand structure-related factors compared with innovation speed.…”
Section: Resultsmentioning
confidence: 99%
“…This section reports on the most salient empirical studies in the literature. Duimering et al (2006) found that project task structure changes as a function of ambiguity. Carbonell and Rodriguez (2006) found a moderating influence of technical complexity on staffand structure-related factors compared with innovation speed.…”
Section: Resultsmentioning
confidence: 99%
“…Projects exhibit characteristics such as urgency, uncertainty, ambiguity, complexity and uniqueness [10][11][12][13]. Therefore, it is vital that project management education programs and instructors adopt learning aids and teaching strategies that present and discuss these characteristics with a more active approach rather than depending solely on a theoretical approach through emphasizing terms and concepts.…”
Section: Open Accessmentioning
confidence: 99%
“…Patterns related to detail orientation affect the certainty of linkages [67]. The more detail there is in the system descriptions, the higher the certainty about their resulting outcome is, which means a decrease in the complexity due to uncertain linkages.…”
Section: Propositions and Discussionmentioning
confidence: 99%